Cordylobia anthropophaga: a rare surgical emergency in the UK. (15th February 2013) - Lowe, Penelope; Naseem, Salma; Bailey, Charles
Abstract : A 38-year-old healthy Caucasian man presented to the surgical team with a punctured wound on the right side of his scalp. He had been on a month's holiday to Uganda and South Africa. He recalls a painful swelling progressively increasing over 2 weeks. This was associated with sharp shooting pains and swelling on the right side of the face. He sought medical opinion while on holiday. Broad spectrum oral antibiotics were advised. The condition did not settle with the treatment so he consulted his general practitioner (GP) on return. The GP referred him to the surgical team for management of a scalp wound. On examination, a live pulsating larva was seen within a painful 1.5×2 cm puncture wound on the right side of the scalp. The larva was removed. Microbiology identified the larva as Cordylobia anthropophaga. No further treatment was advised. To our knowledge, the patient remains well to date.